2023
DOI: 10.1037/emo0001167
|View full text |Cite
|
Sign up to set email alerts
|

The role of emotion regulation and choice repetition bias in the ultimatum game.

Abstract: Social decision-making is commonly explored in the context of adult responder behavior in the ultimatum game. Responder behavior in the game has been proposed to be the consequence of two competing systems that control behavior: an affective system, which promotes an emotional response to unfair offers, and a deliberative system, which instead encourages a rational response to maximize in-game gains. In a secondary analysis of ultimatum game data in children and adolescents (N = 429), the present study demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 62 publications
3
5
0
Order By: Relevance
“…Here, we found convincing evidence for these effects in an intertemporal choice task across two experiments. This is in line with similar effects reported for other value-based decision tasks (Chung et al, 2023;Herranz-Zarzoso et al, 2020;. We expected to see corresponding biases in attentional processes, such that participants would either show an option-based (where they focus on the same option they chose in the previous trial) or a dimension-based (where they focus on the dimension that favoured their previous choice, such as the monetary dimension after making large or late choices, or the temporal dimension after making small or soon choices) attentional repetition bias.…”
Section: Choice Repetition Bias In Intertemporal Choicesupporting
confidence: 92%
See 2 more Smart Citations
“…Here, we found convincing evidence for these effects in an intertemporal choice task across two experiments. This is in line with similar effects reported for other value-based decision tasks (Chung et al, 2023;Herranz-Zarzoso et al, 2020;. We expected to see corresponding biases in attentional processes, such that participants would either show an option-based (where they focus on the same option they chose in the previous trial) or a dimension-based (where they focus on the dimension that favoured their previous choice, such as the monetary dimension after making large or late choices, or the temporal dimension after making small or soon choices) attentional repetition bias.…”
Section: Choice Repetition Bias In Intertemporal Choicesupporting
confidence: 92%
“…In this paper, we focus on another factor that might impact intertemporal choice if seen as value-based decision making: bias from previous decisions, or more specifically, choice repetition biases. The choice repetition bias (i.e., the tendency to repeat the previous choice and to perform choice repetitions faster than choice switches) has been long established in perceptual decision tasks (Bertelson, 1961;Bonaiuto et al, 2016;Cho et al, 2002;Gao et al, 2009;Remington, 1969;Soetens et al, 1985;Urai et al, 2019) and has recently also been demonstrated in value-based decision tasks (Chung et al, 2023;Herranz-Zarzoso et al, 2020;. Here, we ask if this bias can also be found in intertemporal choice.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In this paper, we focus on another factor that might impact intertemporal choice if seen as value-based decision making: biases from previous decisions, or more specifically, the choice repetition bias. The choice repetition bias (i.e., the tendency to repeat the previous choice and to perform choice repetitions faster than choice switches) has been long established in perceptual decision tasks (Bertelson 1961;Bonaiuto, de Berker, and Bestmann 2016;Cho et al 2002;Gao et al 2009;Remington 1969;Soetens, Boer, and Hueting 1985;Urai et al 2019) and has recently also been demonstrated in value-based decision tasks (Chung et al 2023;Herranz-Zarzoso, Sabater-Grande, and Jaramillo-Gutiérrez 2020;Senftleben, Kruse, et al 2021;. Here, we ask if this bias can also be found in intertemporal choice.…”
Section: Introductionmentioning
confidence: 87%
“…In addition, we see the following two observations as support for potential choice repetition effects in intertemporal choice. First, repetition effects have been found in other value-based decision tasks (i.e., tasks where decisions are not based on objective evidence, but rather on individual subjective values assigned to the decision options) (Chung et al 2023;Senftleben, Kruse, et al 2021;. For example, in several previous studies, we used a gamified decision task where participants had to accumulate points in a limited amount of time.…”
Section: Choice Repetition Bias As Potential Influence On Intertempor...mentioning
confidence: 99%